The new Philippines comprehensive dictionary 8 major dialects. (International Standard Pub., 2003)
This book is the second edition that was recently revised to reflect the language of the modern age where new general and technical terms were added for words that are used today in the field of computer and information technology, art, science, business, politics, media and other subject areas.